Preparation and superficial characterization of drugged cobalt spinel electrodes with copper, Cux Co3-x O4, 0≤x≤1.5 - La Rosa Toro, A. (2006)
Cobalt oxide (Co3O4) and copper-doped cobalt oxide (CuxCo3-xO4) films supported on titanium have been prepared by the thermal decomposition method. The electrodes have been characterized by different techniques like scanning Electron Microscopy (SEM), cyclic voltammetry (CV), and X-Ray photoelectron spectroscopy (XPS). The XPS spectra correspond to a characteristic monophasic Cu-Co spinel oxides when x is below 1. However, when the copper content exceeds that for the stoichiometric CuCo2O4 spinel, a new CuOphase segregates at the surface. The analysis of the surface cation distribution in spinel structure indicates that Cu(II) cation are preferently located in octahedral sites of higher electrochemical activity.